Implementasi Dan Perancangan Sistem Kontrol Akses Terminal Access Controller Pada Perangkat Jaringan Switch - Aditama, Javier; sarwo (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
In large and complex networks, the implementation of centralized AAA services is becoming increasingly important. This service not only improves security but also simplifies the management of user access and ensures that security policies can be applied consistently across the network. Organizations that adopt centralized AAA services can more easily manage user access, identify and respond to security threats, and ensure that security policies and procedures are applied consistently across their network infrastructure. This study focuses on the implementation of Terminal Access Controller Access-Control System (TACACS) as a centralized service for Authentication, Authorization, and Accounting (AAA) on switch network devices at PT XYZ. The results of the study indicate that the implementation of TACACS at PT XYZ has successfully improved access security, ensured comprehensive logging, and provided better control over user activities on the network. In conclusion, TACACS is an effective solution in strengthening security and access management on connected network devices at PT XYZ.